ANALYSIS OF THE INFLUENCE OF CAPITAL AND BUSINESS DURATION ON THE INCOME LEVEL OF SMEs (Case Study at CMC Cake Shop - Rina Iklima; Rizki Nadira; Nazri Ainiya; Safriana Safriana; Irada Sinta (PT. Radja Intercontinental Publishing, 2023)
The development of Micro, Small and Medium Enterprises (MSMEs) in Indonesia is getting faster and more advanced. The problems of obstacles and obstacles faced by MSME entrepreneurs in increasing income are very complex and include several aspects which are closely related to one another, including: lack of managerial skills and skills in operating as well as the absence of legal sources from the company, weak organization and limited marketing, lack of capital both in quantity and sources. Therefore, business actors only get unstable or fluctuating profits in their business, therefore the author wants to examine the Analysis of the Effect of Capital and Length of Business on the Income Level of Umkm Cake Shop Cmc located in Keude Buloh Blang Ara, kec. Kuta Makmur, Kab. North Aceh. The founder and owner of Umkm is Mrs. Marlina, S.Pd. who lives in the village of Ceumeucet, Kec. Kuta Makmur, Kab. North Aceh. The target in this study was the owner of the Cmc Cake Shop. The researcher used a qualitative research approach, namely the interview method used to collect data related to business capital, length of business, and income of UMKM UKM Cake Shop traders. The results of this study indicate that the length of business is very closely related to the income of MSMEs. The long term of business also makes customers believe that these MSMEs are good MSMEs. From this it can be concluded that the relationship between business length and income is positive. Business capital is also one of the variables that play an active role in influencing the income level of UMKM CMC cake shops.